Carbon emissions from South‐East Asian peatlands will increase despite emission‐reduction schemes. (17th July 2018) - Wijedasa, Lahiru S.; Sloan, Sean; Page, Susan E.; Clements, Gopalasamy R.; Lupascu, Massimo; Evans, Theodore A.
Abstract: Carbon emissions from drained peatlands converted to agriculture in South‐East Asia (i.e., Peninsular Malaysia, Sumatra and Borneo) are globally significant and increasing. Here, we map the growth of South‐East Asian peatland agriculture and estimate CO2 emissions due to peat drainage in relation to official land‐use plans with a focus on the reducing emissions from deforestation and degradation (REDD+)‐related Indonesian moratorium on granting new concession licences for industrial agriculture and logging. We find that, prior to 2010, 35% of South‐East Asian peatlands had been converted to agriculture, principally by smallholder farmers (15% of original peat extent) and industrial oil palm plantations (14%). These conversions resulted in 1.46–6.43 GtCO2 of emissions between 1990 and 2010. This legacy of historical clearances on deep‐peat areas will contribute 51% (4.43–11.45 GtCO2 ) of projected future peatland CO2 emissions over the period 2010–2130. In Indonesia, which hosts most of the region's peatland and where concession maps are publicly available, 70% of peatland conversion to agriculture occurred outside of known concessions for industrial plantation development, with smallholders accounting for 60% and industrial oil palm accounting for 34%. Of the remaining Indonesian peat swamp forest (PSF), 45% is not protected, and its conversion would amount to CO2 emissions equivalent to 0.7%–2.3% (5.14–14.93 Gt) of global fossil fuel and cement emissions released between 1990 and 2010. Of the peatland extent included in the moratorium, 48% was no longer forested, and of the PSF included, 40%–48% is likely to be affected by drainage impacts from agricultural areas and will emit CO2 over time. We suggest that recent legislation and policy in Indonesia could provide a means of meaningful emission reductions if focused on revised land‐use planning, PSF conservation both inside and outside agricultural concessions, and the development of agricultural practices based on rehabilitating peatland hydrological function. Abstract : Past and future emissions due to drainage based agriculture of Southeast Asian peatlands.